Solution and Solid State Studies of Urea Derivatives of DITIPIRAM Acting as Powerful Anion Receptors - Niedbała, Patryk (Molecules, 2021)
Herein, we present the synthesis and anion binding studies of a family of homologous molecular receptors 4–7 based on a DITIPIRAM (8-propyldithieno-[3,2-b:2′,3′-e]-pyridine-3,5-di-amine) platform decorated with various urea para-phenyl substituents (NO(2), F, CF(3), and Me). Solution, X-ray, and DFT studies reveal that the presented host–guest system offers a convergent array of four urea NH hydrogen bond donors to anions allowing the formation of remarkably stable complexes with carboxylates (acetate, benzoate) and chloride anions in solution, even in competitive solvent mixtures such as DMSO-d(6)/H(2)O 99.5/0.5 (v/v) and DMSO-d(3)/MeOH-d(3) 9:1 (v/v). The most effective derivatives among the series turned out to be receptors 5 and 6 containing electron-withdrawing F- and -CF(3) para-substituents, respectively.